Pengaruh Total Asset Turnover, Return on Asset, Struktur Aset, dan Ukuran Perusahaan terhadap Kebijakan Hutang - Primita, Juika; Rolanda, Ivo (Penerbit Goodwood, 2024)
Purpose: To assess the impact of total asset turnover, return on assets, asset structure, and company size on debt policy in companies within the automotive and component subsectors listed on the Indonesia Stock Exchange for the period 2016-2021. Methodology/approach: The research sample consists of 13 companies in the automotive and component subsectors listed on the Indonesia Stock Exchange for the period 2016-2021, using the Purposive Sampling technique. Multiple linear regression analyses were conducted using SPSS version 22. Results/findings: The results indicate that total asset turnover and return on assets have a significant negative impact on Debt Policy. However, Asset Structure and Company Size do not have an impact on Debt Policy. Limitations: This study only utilizes 4 (four) independent variables: total asset turnover, return on assets, asset structure, and company size. The period considered was only 6 years, from 2016 to 2021. This study focuses exclusively on manufacturing companies within the automotive and component subsectors listed on the Indonesia Stock Exchange (IDX). Contribution: The results of this research are expected to assist companies in making decisions and considerations to optimize their operations in line with the company's objectives. To enhance their size, companies are advised to manage and utilize resources, such as assets, debts, and equity, effectively and efficiently. With proper management, this attracts investors to invest in their capital.